Antibacterial/Antifungal Activity and Synergistic Interactions between Polyprenols and Other Lipids Isolated from Ginkgo Biloba L. Leaves - Ran Tao; Cheng-Zhang Wang; Zhen-Wu Kong (Molecules, 2013)
Polyprenols separated from lipids are promising new components from Ginkgo biloba L. leaves (GBL). In this paper, ginkgo lipids were isolated by extraction with petroleum ether, saponification, and molecular distillation. Eight known compounds: isophytol (1), nerolidol (2), linalool (3), β-sitosterol acetate (4), β-sitosterol (5), stigmasterol (6), ergosterol (7), β-sitosterol-3-O-β-D-glucopyranoside (8) and Ginkgo biloba polyprenols (GBP) were separated from GBL by chromatography and identified mainly by NMR. The separated and identified compounds 1, 2 and 3 are reported here for the first time in GBL. The 3D-DAD-HPLC-chromatogram (190–232 nm) of GBP was recorded. This study provides new evidence as there are no previous reports on antibacterial/antifungal activities and synergistic interactions between GBP and the compounds separated from GBL lipids against Salmonella enterica, Staphylocococus aureus and Aspergillus niger. Nerolidol (2) showed the highest activity among all the tested samples and of all mixture groups tested the GBP with isophytol (1) mixture had the strongest synergistic effect against Salmonella enterica among the three tested strains. A proportion of isophytol and GBP of 38.19%:61.81% (wt/wt) was determined by mixture design as the optimal proportion for the synergistic effect of GBP with isophytol against Salmonella enterica.